Pengaruh Produk, Harga, Distribusi, Promosi Terhadap Volume Penjualan Produk Kerajinan Kayu ( Studi pada Kerajinan Kayu Tohu Srijaya di Kota Batu) - Feby Wijianto; Budi Wahono; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThis study aims to determine the effect of product, price, distribution, promotion on the sales volume of handicraft products in Tohu Srijaya Wood Crafts. This research uses non-probability sampling. Data analysis technique using multiple linear regression.The results of his research products have a significant effect on the sales volume of Tohu Srijaya's wooden handicraft products. Price has a significant effect on the sales volume of Tohu Srijaya's wooden handicraft products. Distribution has a significant effect on the sales volume of Tohu Srijaya's wooden handicraft products. Promotion has a significant effect on volume. Keywords               : Product, Price, Distribution, Promotion and Sales Volume